The gene for an inherited form of deafness maps to chromosome 5q31 - King, Mary-Claire (1992)
Primary-i.e., nonsyndromal-postlingual deafness is inherited as an autosomal dominant phenotype in a large kindred in Costa Rica. Genetically susceptible individuals begin to lose hearing at low frequencies at about age 10 years, after language and speaking are learned. Deafness inevitably progresses by age 30 years to bilateral hearing loss of all frequencies. Intelligence, fertility, and life expectancy are normal. The family traces its ancestry to an affected founder born in Costa Rica in 1754. We have mapped the gene for deafness in this kindred to chromosome 5q31, between the markers IL9 and GRL, by linkage analysis involving 99 informative relatives.